x - 2y = -4 is the standard form of equation
Solution:
Given equation is:
![y = (1)/(2)x + 2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/skotqignbadhq174kqcectnz3yqzd8yb86.png)
We have to write the equation in standard form
The standard form of an equation is Ax + By = C
In this kind of equation, x and y are variables and A, B, and C are integers
From given,
![y = (1)/(2)x + 2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/skotqignbadhq174kqcectnz3yqzd8yb86.png)
Simplify the above equation
![y = (x+4)/(2)\\\\2y = x + 4](https://img.qammunity.org/2021/formulas/mathematics/middle-school/qn71g3ldv54zbrycek8tmzskqlru3zh1rw.png)
Shift the variable terms to the left side of the equation and everything else to the right side
![x - 2y = -4](https://img.qammunity.org/2021/formulas/mathematics/middle-school/v4yk3xrf6d4jgtpkuxazovezs17a6pvhr8.png)
Thus the standard form of equation is found